Assessment of Dyeing Properties of Hibiscus sabdariffa on Ostrich Leather - Deniz Kılıçaslan; Mehmet Mete Mutlu; Nilay Örk Efendioğlu (Journal of Advanced Research in Natural and Applied Sciences)
Natural dyestuffs derived from various plants can be used for dyeing processes in the textile and leather industries. Hibiscus sabdariffa, one of these natural dyestuffs, is known to be used in textiles and produces a red color with good dyeing properties. This study aimed to investigate the dyeing effect of Hibiscus sabdariffa flower on leather materials and to determine its dyeing properties. To achieve this, a dye was extracted from Hibiscus sabdariffa, and all wet processes of ostrich skins—an exotic type of leather—were carried out, incorporating the dye extract by adding a mordant during the dyeing process. Both chrome and vegetable tannins were utilized to examine the effects of the tanning process. Extraction yield, pH measurement, color measurement, to-and-fro rubbing fastness tests, and dyestuff exhaustion measurements were conducted. The results indicated that, particularly when the post-mordant process was applied, the extracted dyestuff yielded superior dyeing properties and color results compared to the non-mordant process. The extract from Hibiscus sabdariffa was determined to effectively dye the skins, producing beautiful and satisfying colors, especially when using iron sulfate mordant in vegetable-tanned leathers.